2018
DOI: 10.1021/acsaem.8b00380
|View full text |Cite
|
Sign up to set email alerts
|

Dyad Sensitizer of Chlorophyll with Indoline Dye for Panchromatic Photocatalytic Hydrogen Evolution

Abstract: Photocatalytic H 2 evolution under a wide visible spectral range is a challenging issue. In this work, we report the synthesis of a novel organic dyad consisting of an indoline−rhodanine π-conjugation with a strong absorption in the green region and a chlorophyll derivative with intense absorbance in the purple and red regions. This synthetic dyad (Dyad) was employed as a photosensitizer in the TiO 2 -based system for photocatalytic H 2 evolution with Pt as the assisting catalyst and ascorbic acid (AA) as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Overall, it could be concluded that both the co-sensitized system and the physical mixed system based on Chl and Ind played a role of "1 + 1 > 2" compared to the case of utilizing each of them separately, and their dyad system was further superior due to its broad fullband absorption band, long charge lifetime, strong electron injection ability and high stability under irradiation. [84] Calixarene is a class of macrocyclic compounds composed of methylene bridged phenol units. Due to the adjustable cavity and ability to form host-guest complexes, calixarene plays an important role in the field of supramolecular chemistry as well as crown ether and cyclodextrin.…”
Section: Photosensitizers Constructed With Macrocyclic Compoundsmentioning
confidence: 99%
“…Overall, it could be concluded that both the co-sensitized system and the physical mixed system based on Chl and Ind played a role of "1 + 1 > 2" compared to the case of utilizing each of them separately, and their dyad system was further superior due to its broad fullband absorption band, long charge lifetime, strong electron injection ability and high stability under irradiation. [84] Calixarene is a class of macrocyclic compounds composed of methylene bridged phenol units. Due to the adjustable cavity and ability to form host-guest complexes, calixarene plays an important role in the field of supramolecular chemistry as well as crown ether and cyclodextrin.…”
Section: Photosensitizers Constructed With Macrocyclic Compoundsmentioning
confidence: 99%
“…The successful attempt proved the feasibility of applying Chl derivatives as photocatalyst on water‐splitting systems. To further improve the yield of H 2 evolution, indoline dye (Ind, D102, Figure a) of which methyl ester could be successfully applied to OSC (vide supra), was covalently connected to the C17‐esterifying group of Chl‐18 as in Dyad . The Dyad‐sensitized Pt/TiO 2 photocatalyst exhibited a maximum turnover number (TON) of 1044 after 6 h under continuous light irradiation ( λ > 400 nm).…”
Section: Application Of Chlorophyll Derivatives As Photocatalyst For mentioning
confidence: 99%
“…e) Schematic diagram of the preparation of ZnChl‐9/Ti 3 C 2 T x composites. Reproduced with permission . Copyright 2020, Wiley‐VCH.…”
Section: Application Of Chlorophyll Derivatives As Photocatalyst For mentioning
confidence: 99%
“…Other phenothiazine-and carbazole-based dyes were designed for the same application [60], including a D-π-A-π-A photosensitizer, with benzothiadiazole as auxiliary electron withdrawing unit [61], and, in particular, a dibenzopyrromethene (BODIPY)-conjugated phenothiazine, which gave Pt/TiO 2 high activity up to near-infrared (NIR) region [62]. Different types of photoactive compounds can be included in the design of a dye with specific structure: some D-A-π-A perylene dyes, featuring cyanoacrylic acid and dicyanomethylene rhodamine as the acceptor/anchoring group, combined with a N-annulated perylene donor and a quinoxaline auxiliary acceptor [63]; two triphenylamine-benzimidazole-based dyes bound on TiO 2 , with Cu 2 WS 4 nanocubes as an alternative water splitting co-catalyst to Pt [64]; a particular composite dye, consisting of π-conjugated indoline-rhodanine with a chlorophyll derivative, which induced panchromatic absorption in the visible range, efficient electron transfer, and prolonged stability [65]; a series of dyes with triphenylamine donor, vinyltiophene bridge, and a cationic pyridinium acceptor (cationic D-π-A photosensitizers) [66]. A superior H 2 evolution rate was recently reached with a thioalkyl-substituted tetrathiafulvalene dye on mesoporous TiO 2 [67].…”
Section: Organic Dye-sensitized Tiomentioning
confidence: 99%